Role of 2-D reformatted images of MDCT in evaluation of small bowel obstruction: A case series - Kamini Gupta; Jaswinder Singh; Kavita Saggar; Amandeep Jassi (Wolters Kluwer Medknow Publications, 2013)
The availability of multidetector computed tomography (MDCT) scanners, coupled with imaging workstations that allow multiplanar and three-dimensional (3D) evaluation of isotropic data sets, have allowed improved depiction and characterization of small bowel obstruction (SBO). In this article, we present a series of five cases and emphasize that addition of coronal images to axial images enhance the identification of site and etiology of SBO especially in unusual cases of SBO.